GUS DUR VIEWPOINT AGAINST TRANSNATIONAL ISLAMIC MOVEMENTS IN INDONESIA - Elsa Tiara (AL-QISTHAS: JURNAL HUKUM DAN POLITIK, 2020)
The phenomenon of the diversity of Islamic social movements in the contemporary era has colored various activities and da’wah in the development of Islam. One of the interesting things in recent academic studies is the emergence of the transnational Islamic movement. The formulation of the problem in this study is how the transnational Islamic movement occurred in Indonesia from the point of view of K.H. Abdurrahman Wahid. The purpose of this study is to analyze the transnational movement in Indonesia from the point of view of K.H. Abdurrahman Wahid. This research uses descriptive qualitative method. The data obtained are sourced from secondary data, namely data obtained through journal articles, books, news, and other sources relevant to the research title. The result of this study is that the transnational Islamic movement in Indonesia is inseparable from the rise of Islam in the past. Transnational movements operating in Indonesia include the Muslim Brotherhood, Hizbut Tahrir, and Wahhabis. The ideology adopted is rooted in totalitarian-centralistic ideology and sharia politicization. This transnational Islamic movement has succeeded in infiltrating the lives of the Indonesian people in various ways. This transnational Islamic movement turned out to be dangerous for the Indonesian nation. Therefore, a good strategy is needed to avoid the dangers posed by the transnational Islamic movement. Keyword: Transnational Islamic Movement, Abdurrahman Wahid, and Indonesia.